The Relationship between Parenting and PMT with Stunting Incidents in Gedangkulut Village, Cerme District - Zahro, FATIMATUZ; Zuhroh, Diah Fauzia; Ernawati (Jurnal Keperawatan Widya Gantari Indonesia, 2023)
Introduction : Stunting is a chronic condition characterized by a lack of energy and protein intake, resulting in impaired growth as reflected by measuring height for age over a long period of time. Provision of additional food which is also known as PMT is deemed necessary for optimal growth and development of children under the age of five. Objective: This study aims to determine the relationship between the practice of preventive maternal therapy and the prevention of stunting in toddlers. The findings indicated that the majority of participants demonstrated appropriate PMT. The method used uses an observational approach, utilizing a case-control research design to distinguish individuals who show stunted growth (groups). The study was conducted in the Gedang Kulut Village area by taking into account the statistics of Monitoring the Nutritional Status of Toddlers which shows that this village has a prevalence of stunting in toddlers of 40, 9%, the proportion of female toddlers (52.9%) was slightly larger than that of males (47.1%). The proportion of toddlers in the age range of 42-59 months is 54.2% higher compared to the age range of 24-41 months which is 45.8%. In conclusion, the findings indicate that certain maternal factors, such as the mother's educational level and history of chronic energy deficiency, as well as parenting styles and differences in practices in providing complementary foods, may contribute to an increased risk of stunting in Gedangkulut Village. Discussion: Toddler age, when development and growth occurs quickly. More nutrients must be consumed at the age of five for optimal growth and development. Stunting has a significant negative impact on a child's future life. Stunted children need a balanced nutritional intake for their growth and development period. Mothers can stop stunting with PMT, and toddlers get healthy nutrition.